2019
DOI: 10.18632/aging.102561
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CARD6 attenuates spinal cord injury (SCI) in mice through inhibiting apoptosis, inflammation and oxidative stress associated ROS production

Abstract: Spinal cord injury (SCI) causes long-term and severe disability, influencing the quality of life and triggering serious socioeconomic consequences. Lack of effective pharmacotherapies for SCI is largely attributable to an incomplete understanding of its pathogenesis. Caspase recruitment domain family member 6 (CARD6) was initially suggested to be a protein playing significant role in NF-κB activation. However, the effects of CARD6 on SCI progression remain unknown. In this study, the wild type (CARD6+/+), CARD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 64 publications
(85 reference statements)
0
19
0
Order By: Relevance
“…45 Gu et al 46 In another recent study, CARD6, Caspase recruitment domain family member 6, was shown to be a key molecular which could inhibit apoptosis by decreasing Cyto-c release to cytosol from mitochondria and inhibition of Caspase-3 signalling pathway. 50 Zhang et al firstly performed a rat model of SCI, and upregulated p38 was related to inflammation and apoptosis after SCI. Zhang et al also suggested that p38 inhibitor SB203580 treatment could alleviate secondary SCI by suppressing inflammation and apoptosis.…”
Section: The Role Of Ap Op Tos Is In S Pinal Cord Inj Urymentioning
confidence: 99%
“…45 Gu et al 46 In another recent study, CARD6, Caspase recruitment domain family member 6, was shown to be a key molecular which could inhibit apoptosis by decreasing Cyto-c release to cytosol from mitochondria and inhibition of Caspase-3 signalling pathway. 50 Zhang et al firstly performed a rat model of SCI, and upregulated p38 was related to inflammation and apoptosis after SCI. Zhang et al also suggested that p38 inhibitor SB203580 treatment could alleviate secondary SCI by suppressing inflammation and apoptosis.…”
Section: The Role Of Ap Op Tos Is In S Pinal Cord Inj Urymentioning
confidence: 99%
“…Previous studies have shown that SCI can lead to the death of a large number of neurons, the rupture of axons, and the formation of dense glial scar to block axon growth and elongation ( Wang et al, 2019 ; Ma et al, 2020 ; Tran et al, 2020 ). These pathological changes could result in severe motor sensory dysfunction ( Su et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the primary injury is the result of physical forces including compression, shearing, laceration and acute stretch/distraction that induced by the initial traumatic events, and often determines the injury severity of SCI. The primary injury is followed by a cascade of secondary injury events that characterized by multiple injury processes including in ammation, glutamate excitotoxicity, apoptosis and free radical-induced cell death, and serves to expand the zone of injured neural tissue and exacerbates neurological de cits and outcomes [3]. The in ammatory responses including the activation of resident microglia, recruitment of macrophages, neutrophils and lymphocytes from the bloodstream to the injury site, lead to profound neuropathological consequences such as neuronal death as well as axonal degeneration and demyelination, and the formation of glial scars [4].…”
Section: Introductionmentioning
confidence: 99%